The Progress of the Helicopter-Borne Transient Electromagnetic Method and Technology in China - Xin Wu; Guoqiang Xue; Yiming He (IEEE Access, 2020)
The central and western regions of China have appropriate conditions for mining development, but there are many deserts, swamps and forest-covered areas in this vast land. As a result, the traditional on-ground methods are difficult to carry out efficiently in these areas. The airborne transient electromagnetic method can implement detection over large areas rapidly and efficiently, and play an important role in terms of resource and environment detection. In recent years, two Helicopter-borne Transient electromagnetic (HTEM) systems, CHTEM-I and CAS-HTEM, were developed in China. In this paper, the difficult issues in the development of HTEM hardware and software will be analyzed, firstly. By tracing the specific technical paths to solve these difficult issues, the latest research achievements in the development process of CHTEM-I and CAS-HTEM will be expounded. Finally, we would like to briefly discuss the research and development direction of HTEM technology in China to promote further development of the research and application of this technology.